2020
DOI: 10.1097/mpg.0000000000002537
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Insufficiency in Children With Eosinophilic Esophagitis Treated With Topical Corticosteroids

Abstract: Objectives: The aim of the study was to identify practices of gastroenterologists screening for adrenal insufficiency (AI) and report prevalence of AI in children with eosinophilic esophagitis (EoE) treated with topical corticosteroids (TCS); compare serum dehydroepiandrosterone sulfate (DHEA-S) levels to morning serum cortisol (MSC) levels as screening tool for AI. Methods: A multipart study was conducted. In part 1, a survey about screening practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…There have been several articles describing adrenal insufficiency after prolonged oral glucocorticoid intake for EoE. [20][21][22][23][24][25] These effects are more pronounced when the patient is on additional steroids for conditions like atopic dermatitis, asthma, or allergic rhinitis. 25 Adrenal insufficiency has been seen with both oral budesonide and fluticasone propionate.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several articles describing adrenal insufficiency after prolonged oral glucocorticoid intake for EoE. [20][21][22][23][24][25] These effects are more pronounced when the patient is on additional steroids for conditions like atopic dermatitis, asthma, or allergic rhinitis. 25 Adrenal insufficiency has been seen with both oral budesonide and fluticasone propionate.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, STS are well tolerated, but there have been consistent reports of AI. With recent estimates of AI incidence in this population ranging from 5% to 10% (6,7,9) many EoE patients are at risk of significant morbidity, and attempts should be made to avoid AI and address it quickly once it occurs. In this study, we report our experience with 32 STS-treated EoE subjects (obtained from approximately 440 subjects with morning cortisol testing, data not shown) who were diagnosed with AI and compare them to 81 STS-treated EoE controls without AI to investigate factors that increase AI likelihood.…”
Section: Discussionmentioning
confidence: 99%
“…To date, of the systemic complications, only the development of AI has been demonstrated. A variety of risk factors for AI development have been suggested and a broad range of incidence rates from 0% to 66% have been reported in the setting of variable methodologies used for screening and diagnosis of AI (6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a condition of inadequate production of steroid hormones by adrenal glands, mainly cortisol; however, the aldosterone production can also be impaired. Recently, a children-based study reported 5% of cases of EoE, who were treated with topical corticosteroids, presented with adrenal insufficiency [126]. However, more data and research work are required to assess the efficacy of screening adrenal insufficiency in patients with EoE.…”
Section: Adrenal Insufficiencymentioning
confidence: 99%